ECLOGITE-FACIES SEA-FLOOR HYDROTHERMALLY-ALTERED ROCKS: CALCULATED PHASE EQUILIBRIA FOR AN EXAMPLE FROM THEWESTERN ALPS AT SERVETTE - Rebay, Gisella; Powell, Roger (Ofioliti, 2012)
In the St. Marcel Valley at Servette in the Western Alps metabasic rocks crop out that were variably altered in a sea-floor hydrothermal system. Successively, they were metamorphosed to eclogite facies. This was used as an opportunity to explore the range of eclogite-facies mineral assemblages that can develop in such altered rocks. The continuum is represented qualitatively by a series of rock-types: eclogite, glaucophanite, talc schist and chlorite schist, with increasing alteration, supposed to all have involved eclogite-facies mineral assemblages. Later, they were variably retrogressed under greenschist-facies conditions. The eclogite-facies mineral assemblages developed from the broad alteration trend represented by the four rock-types have been forward-modelled in terms of three composition vectors. P-T pseudo-sections for the compositions used to represent the rock-types suggest that a P-T of about 22 kbar and 600°C is consistent for the conditions of formation of the rock-types. T-X pseudo-sections along the composition vectors are used to represent the alteration continuum showing the way the mineral assemblages are affected by the degree of alteration.